The Nature of Learning Psychology in Teaching Interaction and the Learning Process - Abu Bakri PASARIBU; Khairunnikmah HARAHAP; Soufy Atma ZAKI; Masyitah MASYITAH (PT Keberlanjutan Strategis Indonesia, 2025)
Learning psychology is a crucial component in education because it serves as a foundation for understanding the dynamics of interactions between teachers and students. This article aims to analyze the nature of learning psychology in the context of teaching and learning processes. Through a library research approach, the discussion focuses on understanding learning psychology theories such as behaviorism, cognitive, constructivism, and humanism, and their application in creating an effective, enjoyable, and adaptive learning process to meet students' needs. The study results indicate that educational psychology plays a significant role in supporting teachers in developing relevant learning strategies, recognizing student characteristics and needs, motivating learning, and creating a conducive learning environment. Therefore, mastery of educational psychology is a primary requirement for teachers to optimally carry out their professional role in educating and guiding students towards holistic development, both intellectually, emotionally, and socially. Educational psychology plays a strategic role in the teaching and learning process, particularly in helping educators understand student characteristics, design appropriate learning methods, and create a classroom atmosphere that supports learning development.